Beyond funds raised: how public displays of compassion manifest in crowdfunding campaigns - Syeb, S; Wuillaume, A; Shepherd, D; Maitlis, SL (Academy of Management, 2021)
Crowdfunding enables the organizing of support for victims of a tragedy from a wide range of sources. While this support can be financial and non-financial, we know relatively little about the non-financial support donors provide. Donors’ words can have substantial positive and negative effects on sufferers; however, donors are also often limited in the extent to which they can provide relevant support due to unfamiliarity with sufferers’ lives. Therefore, it is important to investigate the messages donors leave on campaign pages. In this inductive study, we investigate online responses to a school shooting to explain how donors’ responses to charitable crowdfunding campaigns manifest. The emergent crowdfunding model of public displays of compassion suggests two core types of responses depending on the nature of the public appeal. Our insights extend the boundaries of the theory on charitable crowdfunding by illustrating the benefits of relaxing implicit assumptions regarding the nature of value creation and the uniformity of donor responses.